The Application of Sensors in Rehabilitation Medicine - Jiwen QIU; Qing XIA; Yuxin FANG; Meidan ZHAO; Yongming GUO (康复学报)
With the progress of science and technology, sensor technology has been applied in various fields. Combined with sensor technology, rehabilitation medicine provides a greater convenience for rehabilitation assessment and treatment, and improves the effect of various types of rehabilitation training. We reviewed relevant literatures in the last five years to summarize the application of sensors in rehabilitation medicine, in order to provide clear reference for clinical rehabilitation staff.